Kidney dysfunction, systemic inflammation and mental well-being in elderly post-myocardial infarction patients. Issue 1 (December 2017) - Heeres, Rick; Hoogeveen, Ellen; Geleijnse, Johanna; de Goede, Janette; Kromhout, Daan; Giltay, Erik
Abstract Background The aim was to investigate whether mild kidney dysfunction and low-grade inflammation in post-myocardial infarction patients are independently associated with markers of mental well-being (i.e. depressive and apathy symptoms, and dispositional optimism). Methods In post-myocardial infarction patients, kidney function was assessed by estimated glomerular filtration rate (eGFR) calculated from the combined CKD-EPI formula based on serum levels of both creatinine and cystatine C. Systemic inflammation was assessed using high sensitivity C-reactive protein (hs-CRP) levels. The 15-item Geriatric Depression Scale (GDS-15), the 3-item apathy subscale and the 4-item optimism questionnaire (4Q) were used to measure mental well-being and were analyzed using linear multivariable regression analysis. Results Of the 2355 patients, mean age was 72.3 (range 63–84) years and 80.1% were men. After multivariable adjustment, a poorer kidney function was associated with more depressive symptoms (β = -0.084, p  < 0.001), more apathy symptoms (β = -0.101, p  < 0.001), and less dispositional optimism (β = 0.072, p  = 0.002). Moreover, higher levels of hs-CRP were associated with more depressive symptoms (β = 0.051, p  = 0.013), more apathy symptoms (β = 0.083, p  < 0.001) and less dispositional optimism (β = -0.047p  = 0.024). Apathy showed the strongest independent relation with both low eGFR and high hs-CRP. Conclusions In post-myocardial infarction patients, impaired kidney function and systemic inflammation showed a stronger association with apathy than with depressive symptoms and dispositional optimism.